PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2019-2021 - Novi Chandra Saputra; Nurul Despurnama Sary (STIE PEMBANGUNAN TANJUNGPINANG, 2023)
This study aims to determine the effect of financial performance on profit growth. This study has a sample of 15 companies that have been determined by the sample selection technique. The method used in this research is a quantitative research method. The object of research is the property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Data collection is done in 2 ways, namely documentation and literature study. The tool used to test panel data estimation model selection, best model selection test, panel data regression and hypothesis testing is the Statistical Program For Social Science (SPSS) version 29. The results of this study indicate that the current ratio, debt to asset ratio, and total asset turnover has no effect on the profit growth of Property and Real Estate companies listed on the IDX for the 2019-2021 period. It can be concluded that the effect of the current ratio, debt to asset ratio, and total asset turnover listed on the IDX for the 2019-2021 period is 0.6%, while the remaining 99.4% is influenced by other variables not included in this study, including company size , Company Age, Past Sales Rate and Change